2017
DOI: 10.1093/eurheartj/ehx466
|View full text |Cite
|
Sign up to set email alerts
|

Temporal trends in atrial fibrillation recurrence rates after ablation between 2005 and 2014: a nationwide Danish cohort study

Abstract: One year risk of recurrent AF following first-time ablation has almost halved from 2006 to 2014. Hypertension, female sex, cardioversion 1 year prior to ablation, and AF duration for more than 2 years all increased the associated risk of recurrent AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
68
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(79 citation statements)
references
References 20 publications
8
68
2
1
Order By: Relevance
“…However, real-world data from Denmark have been used to show reductions in AF-related clinical encounters after AF ablation from 2005 to 2014, suggesting secular improvements in AF ablation effectiveness. 19 In a contemporary and rigorous review of the literature, we did not detect any improvements in NPAF ablation efficacy over time. Importantly though, incremental gains in PAF procedural success appear to have occurred, with important caveats and implications.…”
Section: Discussionmentioning
confidence: 67%
“…However, real-world data from Denmark have been used to show reductions in AF-related clinical encounters after AF ablation from 2005 to 2014, suggesting secular improvements in AF ablation effectiveness. 19 In a contemporary and rigorous review of the literature, we did not detect any improvements in NPAF ablation efficacy over time. Importantly though, incremental gains in PAF procedural success appear to have occurred, with important caveats and implications.…”
Section: Discussionmentioning
confidence: 67%
“…Several predictors of mid-and long-term recurrence have been described. Some studies found a statistically significant independent association between AF history duration prior to radiofrequency ablation and recurrence after the procedure, [2][3][4][5] whereas this relationship has not been reported in other series. [6][7][8][9][10] Clarification of this issue might have important implications since there seem to be a tendency to postpone catheter ablation in patients with a short clinical history of AF.…”
Section: Introductionmentioning
confidence: 78%
“…The influence of age and hypertension did not reach statistical significance, while BMI was not reported. A recent Danish nationwide cohort study investigated the 1 year risk of AF recurrence following first time ablation in 5425 patients . Female sex (OR 1.20; 95% CI 1.06‐1.37) AF duration >2 years (OR 1.14; 95% CI 1.01‐1.28), hypertension (OR 1.23; 95% CI 1.09‐1.38) and cardioversion in the year prior to ablation (OR 1.40; 95% CI 1.17‐1.67) all predicted AF recurrence, while BMI was not reported.…”
Section: Discussionmentioning
confidence: 99%